Community motivations to engage in conservation behavior to conserve the Sumatran orangutan. Issue 4 (6th April 2016) - Nilsson, Danielle; Gramotnev, Galina; Baxter, Greg; Butler, James R.A.; Wich, Serge A.; McAlpine, Clive A.
Abstract: Community‐based conservation programs in developing countries are often based on the assumption that heteronomous motivation (e.g., extrinsic incentives such as economic rewards and pressure or coercion to act) will incite local communities to adopt conservation behaviors. However, this may not be as effective or sustainable as autonomous motivations (e.g., an intrinsic desire to act due to inherent enjoyment or self‐identification with a behavior and through freedom of choice). We analyzed the comparative effectiveness of heteronomous versus autonomous approaches to community‐based conservation programs through a case study of Sumatran orangutan (Pongo abelii) conservation in 3 villages in Indonesia. Each village had a different conservation program design. We surveyed people (n = 240) to determine their motivations for and behavior changes relative to orangutan and orangutan habitat (forest) protection. Heteronomous motivations (e.g., income from tourism) led to greater self‐reporting of behavior change toward orangutan protection. However, they did not change self‐reported behavior toward forest (i.e., orangutan habitat) protection. The most effective approach to creating self‐reported behavior change throughout the community was a combination of autonomous and heteronomous motivations. Individuals who were heteronomously motivated to protect the orangutan were more likely to have changed attitudes than to have changed their self‐reported behavior. These findings demonstrate that the current paradigm of motivating communities in developing countries to adopt conservation behaviors primarily through monetary incentives and rewards should consider integrating autonomous motivational techniques that promote the intrinsic values of conservation. Such a combination has a greater potential to achieve sustainable and cost‐effective conservation outcomes. Our results highlight the importance of using in‐depth sociopsychological analyses to inform the design and implementation of community‐based conservation programs.